Giyugun : cikal-bakal Tentara Nasional di Sumatera - Zed, Mestika, 1955-; Aiko, Kurasawa (Jakarta : LP3ES, 2005)
History of Giyugun, the Japanese trained Indonesian army during Japanese occupation in Indonesia, 1942-1945 and their role in the formation of Indonesian Armed Forces in Sumatera Island.
Bibliografi: p. [226]-243.
Keywords: Military ethics -- Indonesia; Indonesia -- History -- Revolution, 1945-1949.; Indonesia -- Armed forces